Zinc Oxide Nanostructures Grown Using Electric Field-Assisted Aqueous Solution Method For Uv Photodetector Applications - Dalvand, Ramazanali (2019)
Nanostructured zinc oxide (ZnO) was successfully synthesized using an electric field-assisted aqueous solution (EFAS) technique. ZnO nanostructures were grown with different growth parameters and characterized for the structural, optical and electrical properties. The study employed ZnO-seeded porous silicon (PSi) to grow one-dimensional (1-D) ZnO nanostructures. ZnO nanorod arrays were synthesized via the optimization of current density by using EFAS method and the ZnO nanorods were grown on PSi substrates that were prepared via a photo electrochemical etching (PECE) technique. Vertically aligned needle-shaped ZnO sample prepared at a current density of 0.5 mA/cm2, growth temperature of 105 °C, precursor concentration of 50 mM, and growth duration of 60 minutes produced the optimal structural, morphological, and optical properties with the highest (002) XRD peak intensity. Moreover, photoluminescence (PL) data of the optimized sample revealed the highest near-band-edge emission to deep-level emission intensity ratio while Raman data showed the most intense E2 (high) phonon mode compared with that of other samples. Using the optimized precursor concentration in the EFAS method, 1-D ZnO nanostructure arrays were grown on PSi subtrates. 1-D ZnO nanorods with cone heads were produced using the EFAS technique when the growth parameters were tuned at 50 mM precursor concentration, 0.65 mA/cm2 current density, 105 °C growth temperature and 60 minutes growth duration.